Developing an In-House Training Model for Digital Pedagogical Competence of Islamic Religious Education Teachers - Adah Aliyah; Mahmud Mahmud; Bambang Samsul Arifin; Asep Nursobah; Ana Rohana Pataniah binti Salahuddin (Badan Litbang dan Diklat Kementerian Agama RI, 2026)
The digital transformation of education demands stronger digital pedagogical competence among Islamic Religious Education (IRE) teachers. This study aimed to develop, implement, and evaluate a contextual In-House Training (IHT) model using the Four-D framework (Define, Design, Develop, Disseminate). A mixed-methods sequential explanatory design was employed. Needs analysis involved 40 IRE teachers from 23 junior high schools; the development phase (limited trial) involved 20 teachers; the dissemination phase (full implementation) involved 40 teachers (the original 20 plus 20 additional teachers trained through peer-training). Data were collected through questionnaires (Cronbach's alpha 0.89), interviews, observations, and documentation. The model significantly improved digital lesson planning (from 45% to 82%, p < 0.01, d = 1.24), active learning strategies (68%), and educational app mastery (75%). Systemic effects included a 65% increase in digital media use and 30% reduction in preparation time. The novelty lies in operationalizing TPACK within IRE through a school‑based, practice‑oriented IHT model that explicitly integrates Islamic values. This study contributes a replicable prototype for digital religious pedagogy in developing countries. ABSTRAK Transformasi digital pendidikan menuntut kompetensi pedagogik digital yang lebih kuat bagi guru Pendidikan Agama Islam (PAI). Penelitian ini bertujuan mengembangkan, mengimplementasikan, dan mengevaluasi model In-House Training (IHT) kontekstual menggunakan kerangka Four-D. Desain sequential explanatory mixed-methods digunakan. Analisis kebutuhan melibatkan 40 guru PAI dari 23 SMP; tahap pengembangan (uji terbatas) melibatkan 20 guru; tahap diseminasi (implementasi penuh) melibatkan 40 guru (20 guru awal ditambah 20 guru tambahan melalui peer-training). Data dikumpulkan melalui kuesioner (Cronbach's alpha 0,89), wawancara, observasi, dan dokumentasi. Model IHT meningkatkan signifikan penyusunan RPP digital (45% ke 82%, p<0,01, d=1,24), strategi pembelajaran aktif (68%), dan penguasaan aplikasi pendidikan (75%). Dampak sistemik meliputi peningkatan penggunaan media digital sebesar 65% dan pengurangan waktu persiapan mengajar sebesar 30%. Kebaruan penelitian ini terletak pada pengoperasionalan TPACK dalam konteks PAI melalui model IHT berbasis sekolah dan berorientasi praktik yang secara eksplisit mengintegrasikan nilai-nilai Islam.